Superior Mesenteric Artery Syndrome Associated with Rapid Weight Loss Attributed to Amphetamine Abuse. (13th August 2015) - Fazio, Richard M.; Chen, On; Eldarawy, Wael
Abstract : Superior mesenteric artery (SMA) syndrome arises from a reduction in the angle formed between the SMA and the aorta, thereby compressing the third portion of the duodenum. This phenomenon may be caused by a number of factors, one of which being acute weight loss. We report a case of a female patient presenting with abdominal pain and vomiting who developed superior mesenteric artery (SMA) syndrome as a result of rapid weight loss, thought to be secondary to amphetamine abuse. This association can often be overlooked and, to our knowledge, has not been previously reported.